Posttraumatic hydrocephalus as a complication of decompressive craniectomy–same old story, new perspectives - Șerban, Nicoleta-Larisa; Florian, Ioan Stefan; Florian, Ioan Alexandru; Atena Zaha, Andreea; Ionescu, Daniela (Frontiers in Surgery, 2024)
Objective: Decompressive craniectomy (DC) serves as a vital life-saving intervention, demonstrating efficacy in reducing intracranial pressure (ICP). However, its efficacy hinges on meticulous surgical execution, perioperative management, and vigilance toward potential complications. The incidence of complications associated with DC plays a pivotal role in determining its superiority over medical management for patients experiencing intracranial hypertension following traumatic brain injury (TBI).Methods: Severe cases often require more intensive therapy, prolonged mechanical ventilation, and vasopressor treatment. Identifying the optimal moment for early extubation and minimizing vasopressor use is crucial to reducing the risk of complications, including PTH.Our study aims to highlight the potential risks associated with prolonged mechanical ventilation and long-term vasopressor administration. The collected data were demographics, the craniectomy size, the distance from the midline of the craniectomy, the presence or absence of hydrocephalus, duration of mechanical ventilation and vasopressor treatment, and outcome at 30 days.Results: Seventy-two patients with a mean age of 44.2 (range 5-83) were included in the study, with a median craniectomy size of 119.3 cm 2 . In our series, craniectomy areas ranged between 30 and 207.5 cm 2 and had a similar decrease in midline shift in all cases. We did not observe any associations between the surface of craniectomy and the complication rate (p=0.6302).There was no association between craniectomy size and mortality rate or length of hospital stay.The most common complication of decompressive craniectomy in our study group was posttraumatic hydrocephalus, with an incidence of 13.8%. Our results showed that craniectomy size did not independently affect PTH development (p = 0.5125). Still, there was a strong correlation between prolonged time of vasopressor treatment (p = 0.01843), period of mechanical ventilation (p = 0.04928), and the development of PTH.Conclusions: This study suggests that there is no clear correlation between craniectomy size, midline shift reduction, and survival rate. An extended period of vasopressor treatment or mechanical ventilation is linked with the development of posttraumatic hydrocephalus. Further studies on larger series or randomized controlled studies are needed to better define this correlation.